ANALISIS FAKTOR YANG MEMPENGARUHI MAHASISWA REGULERMEMILIH STUDI DI UNIVERSITAS DARUSSALAM GONTOR - Agung Khoirudin, Imron; Amalia Kurniawan, Dhika (Widya Warta, 2019)
This study aimed to determine the effect of pesantren university image and quality of education on the decision of regular students to choose pesantren universities at University of Darussalam (UNIDA) Gontor Ponorogo. This research was motivated by 1) high interest of individuals to pursue their education to pesantren based university, 2) inadequate amount of Islamic boarding schools or pesantren in Indonesia. 3) increasing number of regular students at University of Darussalam (UNIDA) Gontor through-out the year, 4) institutional image and quality of education able to influence students' decision making on choosing pesantren universities. The population in this study were regular students (non graduates of Gontor Modern Islamic Boarding School) who were active from 2014 to 2017 whose total was 174 students. Using Non-probability sampling techniques, this research took samples from regular students in semester 3 to 8 considering that students in semester 1 or 2 were on an adjustment period. Data analysis techniques used included validity test, reliability test, classical assumptions test, and multiple linear regression. The result indicated that the university image variable had positive and significance effect on decision making of regular students in choosing pesantren universities and the quality of education variable also had positive and significant effect on decision of regular students in choosing pesantren universities at University of Darussalam (UNIDA) Gontor. Furthermore the most impactful variables to the decision making of regular student in choosing pesantren university was the quality of education variable. Subsequently those results have suggestions as follows: (1) University of Darussalam (UNIDA) Gontor should always increase the factors which influence positive vibes on interest of regular students in deciding to take undergraduate degrees in that particular university. (2) Variables and indicators in this research are universal and un-bind, hence further research are expectedÂ  to add more variables in order to obtain results able to develop a model in the study.